Influence of C60 fullerenes on the glass formation of polystyrene. (26th June 2015) - Sanz, Alejandro; Wong, Him Cheng; Nedoma, Alisyn J.; Douglas, Jack F.; Cabral, João T.
Abstract: We investigate the impact of fullerene C60 on the thermal properties and glass formation of polystyrene (PS) by differential scanning calorimetry (DSC) and dielectric spectroscopy (DS), for C60 concentrations up to 30% mass fraction. The miscibility and dispersibility thresholds of PS/C60 nanocomposites are first estimated by a combination of microscopy, small angle neutron scattering (SANS) and wide-angle X-ray scattering (WAXS) experiments, and these thresholds were found to be ≃1 mass% and ≃4 mass% C60, respectively. The addition of C60 increases the glass-transition temperature ( T g ) of rapidly precipitated PS composites, up to a 'threshold' C60 concentration (≃4 wt%, in agreement with the dispersibility estimate). Beyond this concentration, the T g reverts gradually towards the neat PS value. We present a comprehensive study for composites based on PS of molecular mass 270 kg/mol, and demonstrate the generality of the impact of C60 on T g for PS matrices of 2 and 20 kg/mol. Thermal annealing or slowly evaporated composites largely reverse these effects, as the dispersion quality decreases. The dynamic fragility m of the composite is found to increase in the presence of C60, but the scaling of m with T g for PS is retained. Similarly, physical ageing experiments show a reduction of relaxation enthalpy in the glass regime, which is largely accounted for by the increase of T g with C60 . The slowing down of the PS α -relaxation with C60 contrasts with the local 'softening' indicated by former Debye-Waller measurements and increase in fragility m . This effect is opposite to that of antiplasticizer additives, which both stiffen the material in the glassy state and reduce T g, and simulations suggest this could be due to an increase in packing frustration. Finally, we review observations on the effect of nanoparticles on the T g of PS and discuss the non-universal nature of T g shifts by various types of nanoparticles. Graphical abstract: Highlights: C60 fullerenes increase glass transition temperature and fragility of well-dispersed poly(styrene) nanocomposites. Fullerenes increase local fast dynamics and slow down segmental glassy dynamics, interpreted as due to packing frustration. Upon fullerene aggregation, all dynamic changes are reversed back to the neat polymer behaviour. Polystyrene Tg shifts depend qualitatively on surface interactions and quantitatively on filler loading and dispersion.